Preliminary Model and Simulation towards Crowd Dynamics in Virtual Enviroments - Widyarto, Setyawan; Abd. Latiff, Muhammad Shafie (2005)
This paper is a part of the project entitled Model and Simulation of Crowd Dynamics in Virtual Environments and will approach crowd model through some traffic models. It is aimed to catch the nature of crowd ahead of a crowd simulation, thus, will attain the most significant crowd variables or parameters in controlling crowd movement. The paper will discuss real world representation, model development,model implementation and validation. Eventually, some expected contribution of this work will be summing up this research proposal. The model of environment as real world representation is built based on comparative picture measurement and satellite images. To derive the model, a segment of simulated length dx along a path (area) of crowd events is given. Let Ï(x,t) denote density in units of agents/meter at time t, and v(x,t) denote the velocity of agents in the path with coordinate x at time t in units of meter/second. Also q(x,t) denote the number of agents flowing the path during the time period dt. The conservation laws applied in the model. Whereas, the model will implement crowd during Hajj/Umrah and will be validated by using real parameters.